2011
DOI: 10.1017/s0007114511005150
|View full text |Cite
|
Sign up to set email alerts
|

Fructo-oligosaccharide systemically diminishedd-galactose-induced oxidative molecule damages in BALB/cJ mice

Abstract: Subcutaneous (s.c.) D-galactose (DG) treatment has been shown to facilitate the development of biomarkers for Alzheimer's disease in C57BL/6J mice. The aim of the present study was to determine whether this treatment in young BALB/cJ mice, another mouse strain, enhanced oxidative stress to similar extents shown in older mice, and to further determine the effects of fructo-oligosaccharide (FO), a prebiotic fibre and vitamin E (antioxidant control) on the DG-induced oxidative damage of lipids, proteins and mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
(47 reference statements)
1
22
0
1
Order By: Relevance
“…Given that oxidative processes and other putative mechanisms are responsible for ACR neurotoxicity, the presently observed elevated levels of oxidative markers and protein carbonyl levels detected in the fetal and maternal brain with ACR exposure could in part, account for generation of oxidative free radicals, clearly indicating that fetal brain milieu were indeed subjected to significant oxidative stress. Moreover, prebiotic combination blunted this effect associated with ACR exposure, and this data is consistent with previous reports that have demonstrated that prebiotics can attenuate oxidative damage [13,53]. More importantly our finding corroborates with the previously demonstrated propensity of oligosaccharides to scavenge free radicals in vitro and inhibit lipid peroxidation in vivo [54].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Given that oxidative processes and other putative mechanisms are responsible for ACR neurotoxicity, the presently observed elevated levels of oxidative markers and protein carbonyl levels detected in the fetal and maternal brain with ACR exposure could in part, account for generation of oxidative free radicals, clearly indicating that fetal brain milieu were indeed subjected to significant oxidative stress. Moreover, prebiotic combination blunted this effect associated with ACR exposure, and this data is consistent with previous reports that have demonstrated that prebiotics can attenuate oxidative damage [13,53]. More importantly our finding corroborates with the previously demonstrated propensity of oligosaccharides to scavenge free radicals in vitro and inhibit lipid peroxidation in vivo [54].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, Bifidobacteria numbers in cecum were decreased with ACR exposure, whereas the numbers were significantly greater among ACR dams provided with prebiotic supplements Fig. 1 Body weight changes among dams supplemented with prebiotic oligosaccharides (GD 0-19) and exposed to acrylamide (GD [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Sperm-positive dams were assigned to treatment groups based body weights on GD 0.…”
Section: Modulatory Effect Of Prebiotic Supplements On Cecal Charactementioning
confidence: 99%
See 1 more Smart Citation
“…liver and blood cells (Lei et al, 2008;Xie and Ling, 2008;Aydin et al, 2012;Hsia et al, 2012;Wu et al, 2012) more recently, we found phenotypes of Polycystic Ovary Syndrome (PCOS) in this model (Park and Choi, 2012). These induced phenotypes may be the result of excessive formation of Reactive Oxygen Species (ROS) and D-gal-induced accumulation of AGEs (Song et al, 1999).…”
Section: Ajimentioning
confidence: 76%
“…São produzidos por processos fermentativos, sendo o Bacillus subtilis relatado como um promissor produtor a partir da sacarose (BERTÉ et al, 2013). Os FOS destacam-se devido às suas propriedades fisiológicas, como prebióticos, imunomoduladores, antioxidantes, entre outras (THAKUR et al, 2012;HSIA et al, 2012). Além disso, são caracterizados pela metade da doçura da sacarose (JALAN et al, 2013), se tornando adequados para uso em alimentos de baixa caloria e para o consumo por pessoas com diabetes.…”
Section: Introductionunclassified